Timing Matters: The Impact of Sowing Dates on Photosynthetic Traits and Biomass Accumulation in Hybrid Winter Wheat - Yulu Zhang; Wenlu Li; Zixin Zhu; Ludi Zhao; Hongxiao Duan; Hongmei Ge; Changxing Zhao (Agriculture, 2024)
At present, the use of hybrids is becoming more and more widespread, and the study of its traditional cultivation methods also needs to pay attention to the combination of good seed and good methods to achieve maximum economic benefits. “Good seed” is selected from varieties with high production potential and strong resistance to stress. To investigate the effects of sowing dates on biomass accumulation and photosynthetic characteristics of hybrid winter wheat, this study was conducted over two growing seasons (2021–2023) using a hybrid variety, Jingmai 17, and a conventional variety, Jimai 22. Three sowing dates were tested: October 13 (D1), October 23 (D2), and November 2 (D3). Results indicated that Jingmai 17 had a larger leaf area per culm (LAC) post-anthesis, and a lesser variation in SPAD values throughout the middle and late irrigation phases, leading to enhanced photosynthetic performance and higher biomass accumulation at maturity. It outperformed Jimai 22 by approximately 10% in yield. The optimal sowing date (D2) allowed both varieties to maintain a favorable LAC, which supported higher SPAD values, net photosynthetic rates (Pn), and stomatal conductance (Gs) during late grain filling. Correlation analysis revealed a positive relationship between post-anthesis biomass accumulation and yield, suggesting that increased accumulation at this stage underpins yield formation. Under D2 conditions, Jingmai 17 and Jimai 22 achieved yields of 9603.70 kg·ha−1, 9058.68 kg·ha−1 and 8785.44 kg·ha−1, 8294.89 kg·ha−1, respectively, which are 3.4%, 4.6% and 3.4%, 12.4% higher than under D1 conditions, respectively, and 10.7%, 12.4% and 12.8%, 14.5% higher than under D3 conditions, respectively. D1 had higher thousand-grain weight (TGW) but lower number of grains per unit area (GN); D3 had lower TGW, while the GN was not significantly higher, and D2 was effective in improving seed yield. Overall, Jingmai 17 demonstrated significant photosynthetic and yield advantages, maximizing yield potential through optimal interactions among spike number (SN), grain number per spike, and TGW at the October 23 sowing date.